A qualitative analysis of EFL learners’ task-generated discourse - Baharun, Hazleena; Zakaria, Abd Razak (Science Publishing Group, 2013)
This study examined oral discourse generated by learners of English as a foreign language (EFL) using two different communication task types i.e. jigsaw and decision-making. It investigated how the learners approached and processed the tasks and how they interacted during task completion. The data for the study comprised transcribed recordings of learner interactions working on given tasks. They were qualitatively analysed focusing on the cognitive and social processing. Findings showed that both task types promoted episodes of negotiated interaction when the participants attempted task completion. However, close examination showed that the participants engaged in more intensive negotiations which were exploratory in nature and highly collaborative during decision-making task completion than during task completion of the jigsaw task type. The results suggest that different task types elicited different kinds of interaction from the learners and how the participants approached and processed the tasks shaped the kind of learner interactions they generated.